KAJIAN SEMIOTIK MANTRA PENAWAR ANAK-ANAK MASYARAKAT MELAYU SAMBAS - Putri Putri; A Totok Priyadi; Sesilia Seli (Universitas Tanjungpura, 2019)
AbstractThis study examined the semiotics of the mantra or curing spells on children of the Sambas Malay community. Mantra is a type of oral literature or old literature that has faded among society due to developments over time. This study focused on identifying the symbol and meaning in the mantra, especially the mantra for treating diseases on children in the Sambas Malay society, Makrampai village, Sambas Regency. This study aims to describe the symbol, meaning of the mantra, and its implementation into teaching and learning. This semiotic study was carried out with reference to the theory of Ferdinand The Saussure, and was conducted by applying a qualitative method of which the discussion was presented descriptively from the analysis there are 22 symbols used in the mantra. The mantras are of 18 meanings in which overall have the religious, social, and personality meaning. Accordingly, the results can be used to develop a text or material which can be used in basic competencies 3.7 in the grade Indonesian subjects in subjects in semester 1 the 2013 curriculum.Keywords: curing spells children, Makrampai village, semiotic